Pengaruh Gaya Hidup Hedonis, Kepercayaan, dan Pengalaman Terhadap Niat Kunjung Kembali Ace Hardware - Ella Anastasya Sinambela; Jahroni Jahroni; Samsul Arifin (Jurnal Simki Economic, 2023)
The progress of time makes the needs of human life continue to grow. This phenomenon is the driving force for retail company Ace Hardware to establish a company that provides household appliances. Facing competition can be done by increasing the intention to return to consumers. This study aims to determine the effect of hedonic lifestyle, beliefs, and experiences on intention to return. This study used 154 samples who were Ace Hardware consumers who had visited more than two times. Data obtained through questionnaire responses were analyzed using multiple linear regression. The results of the study show that the hedonic lifestyle influences the intention to return. Research also proves that trust influences intention to return. Furthermore, the intention to return is also influenced by the experience of the consumer.